Method for separating perovskite and preparing battery material based on blast furnace titanium slag
By separating and modifying CaTiO3 from the blast furnace titanium slag, the problem of impurities in the blast furnace titanium slag affecting the quality of titanium-based products is solved, and the material cost is reduced, thereby achieving efficient preparation of the solid electrolyte interface layer of high-stability lithium battery.
Patent Information
- Application Number
- CN202411922891.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The titanium slag of blast furnace contains a large amount of impurities, resulting in poor quality of the prepared titanium-based products. In the prior art, perovskite CaTiO3 needs to be purchased separately, resulting in high material cost.
A process for separation and modification of CaTiO3 in titanium slag of blast furnace was designed. High-purity CaTiO3 was extracted through ball milling, ultrasonic cleaning, acid leaching and other steps, and its morphology was adjusted to adapt to the requirements of the solid electrolyte interface layer of lithium batteries.
The cost of separator preparation is significantly reduced, the thermal stability and cyclic performance of the solid electrolyte interface layer of lithium battery is improved, and the bonding strength with polyethylene separator is enhanced.
Smart Images

Figure CN119905771A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of titanium slag separation, and in particular to a method for separating perovskite and preparing battery materials based on blast furnace titanium slag. Background Art
[0002] Blast furnace titanium slag contains a high proportion (25-85%) of titanium dioxide (TiO 2 ), making it an important raw material for the preparation of titanium-based products. However, in addition to titanium dioxide, blast furnace titanium slag also contains a large amount of impurities. The presence of these impurities makes the quality of titanium-based products prepared based on blast furnace titanium slag poor, which seriously affects the economic value of blast furnace titanium slag. Therefore, it is of great economic significance to develop a new separation and purification technology for blast furnace titanium slag, improve the purity and quality of titanium-based products, and realize the high-value utilization of blast furnace titanium slag.
[0003] At the same time, with the rapid development of electric vehicles, smart grid energy storage devices and portable electronic devices, higher requirements are placed on the energy density and endurance of batteries. Metallic lithium has been considered as one of the most ideal negative electrode materials due to its advantages such as high energy density, low working potential and low density. However, during the cycle of lithium metal batteries, due to uneven lithium deposition and repeated destruction and reconstruction of the fragile solid electrolyte interface (SEI) layer, uncontrollable and harmful lithium dendrite growth is easy to occur. This will not only cause a decrease in coulombic efficiency and rapid decay of cycle performance, but may even lead to safety issues such as puncture of the diaphragm. Although the widely used polyethylene (PE) diaphragm has a certain application basis, its wettability is poor and it is easily penetrated by lithium dendrites during the cycle, causing the diaphragm to fail. Therefore, finding a composite diaphragm material suitable for high energy density lithium metal batteries has become a top priority to improve the performance of lithium metal batteries.
[0004] In response to the above problems, some studies have tried to use PE composite membranes to solve the ion transport problem (for example, "Interface treatment based on calcium carbonate in perovskite solar cells and its mechanism study"). The core idea of these studies is to use perovskite CaTiO 3 As a coating material or coating composite material, it can be used to prepare narrow bandgap oxides with better lithium affinity, thereby improving the performance of the electrolyte interface layer of lithium batteries.
[0005] However, in the prior art, perovskite-type CaTiO 3 Usually, pure products need to be purchased separately, and the demand is large and the purity requirement is high, which leads to high material costs. In order to solve this problem, the inventor proposed an innovative idea: if CaTiO with the properties required for lithium battery modification can be separated from blast furnace titanium slag, 3, which will greatly reduce the cost of diaphragm preparation and provide a new opportunity for the high-value utilization of blast furnace titanium slag. 3 , but it also contains a lot of impurities, and the CaTiO 3 The morphology does not meet the standards required for lithium battery modification and therefore cannot be directly applied.
[0006] In order to overcome this technical difficulty, the inventor first proposed a method for CaTiO 3 After systematically analyzing the composition of blast furnace titanium slag, the inventors designed a targeted separation process to extract high-purity CaTiO from blast furnace titanium slag that meets the requirements for lithium battery modification. 3 In addition, the inventors further proposed a modification method, by adjusting the CaTiO 3 morphology, making it better adapted to the requirements of the solid electrolyte interface layer of lithium batteries, thereby significantly improving the cycle performance and safety of lithium batteries. Summary of the invention
[0007] In order to solve the above problems, the present invention provides a method for separating perovskite and preparing battery materials based on blast furnace titanium slag. The inventors analyzed the components of blast furnace titanium slag and designed a method for separating perovskite and preparing battery materials based on the components of blast furnace titanium slag. 3 and silicate separation process, and further improved the separated CaTiO 3 The microstructure of the film enhances its bonding strength with the polyethylene separator, thereby improving the thermal stability of the solid electrolyte interface layer of the lithium battery, as follows:
[0008] S1, titanium slag impurity removal;
[0009] S1-1, after ball milling, the initial blast furnace titanium slag is ultrasonically cleaned with anhydrous ethanol and deionized water in sequence, and then completely dried and ground into powder for later use, to obtain cleaned titanium slag;
[0010] S1-2, placing the cleaned titanium slag and MnO in a reactor at a molar ratio of Mn:Ti=3-4:8, ball milling and mixing evenly, placing in a reactor after mixing evenly, and then heating from room temperature to 1500°C at a heating rate of 3°C / min and keeping the temperature for 1-1.5h, then cooling at a cooling rate of 1-2°C / min until the temperature is cooled to 1250°C, and quenching in a quenching agent to obtain quenched slag after perovskite precipitation;
[0011] S1-3, the quenched slag is washed with anhydrous ethanol, ball-milled, dried once, acid-leached, filtered, washed with deionized water, and dried twice to obtain CaTiO 3 material;
[0012] Description: Desiliconization is a difficult point in the wet resource recovery process of high-silicon blast furnace titanium slag. The reason is that the dissolved silicate molecules have complex polymerization and gelation behaviors. 3 ) as the target component, and the reconstruction and separation of silicate minerals and CaTiO 3 Enrichment;
[0013] S2. Preparation of CaTiO 3 Composite diaphragm;
[0014] S2-1, CaTiO 3 The material was isostatically pressed at 6 MPa into a sheet with a thickness of 0.7 to 1 mm to obtain CaTiO 3 Thin slices;
[0015] S2-2, calcium glycerophosphate, Ca(CH 3 COO 2 , EDTA-2Na and NaOH are mixed evenly in deionized water to obtain a mixed solution;
[0016] Let n be the multiplication coefficient and n∈R + , then the amount of calcium glycerophosphate added to the mixture is 10 ng, Ca(CH 3 COO 2 The amount of added was n[11.5,12.8]g, the amount of added EDTA-2Na was n[14.3,.15.5]g, the amount of added NaOH was n[9,10]g, and the amount of added deionized water was n[1,1.2]L;
[0017] S2-3, S2-3, place the mixed solution in S2-2 into the arc oxidation equipment as electrolyte, use the stainless steel tank as the working cathode, and use the CaTiO 3 The thin sheet is used as the working anode, and finally oxidized by electricity to obtain a porous network of CaTiO 3 ;;
[0018] S2-4, the porous network CaTiO 3 Completely immersed in NaOH solution for etching, and then crushed to obtain CaTiO 3 Composite materials;
[0019] S2-5, CaTiO 3 The composite material and the adhesive are stirred and mixed uniformly, and then sprayed uniformly on both sides of the PE diaphragm, and then dried to obtain CaTiO 3 Composite diaphragm.
[0020] Furthermore, the parameters of ultrasonic cleaning in S1-1 are: ultrasonic frequency of 40-50 kHz, cleaning temperature of 45-55°C, and cleaning time of 20-30 min.
[0021] Furthermore, the parameters of ball milling in S1-2 are: ball mill speed is 200-250 r / min, ball milling time is 1-1.5 h;
[0022] The quenching agent in S1-2 is 20% by mass of NaNO 3 and 25% by mass of Na 2 CO 3 Mix in a volume ratio of 2 to 4:1.
[0023] Note: The selection of quenching temperature and quenching agent will lead to changes in the microstructure of perovskite in the quenched slag; the quenching rates of oil quenching and water quenching are different, and the cooling rate of oil quenching is slower than that of water quenching. Therefore, the surface of titanium slag after oil quenching is smooth, while the surface of titanium slag after water quenching is loose. Based on the adhesion strength of other components on perovskite in subsequent processes, the water quenching process is selected here; it is worth noting that the content of silicon impurities in titanium slag after oil quenching is lower than that in titanium slag after water quenching; the water quenching process is selected here because perovskite (CaTiO 3 ) morphology on the subsequent composite diaphragm strength.
[0024] Further, the parameters of acid leaching in S1-3 are: leaching temperature is 25°C, the leaching liquid is 10% hydrochloric acid by mass, the solid-liquid ratio is 1:15-20, the leaching time is 1h, and the stirring rate during acid leaching is 400-450r / min;
[0025] The parameters of ball milling in S1-3 are: ball mill speed is 200-250 r / min, ball milling time is 1-1.5 h;
[0026] The parameters of the primary drying and secondary drying in S1-3 are: the drying temperature is 100°C and the drying time is 30 to 40 minutes.
[0027] Description: By adding a special quenching agent, the low-valent titanium (+2, +3) present in the silicate mineral phase is oxidized to +4 and enriched in the perovskite phase. The silicate phase that cannot be completely dissolved by acid is reconstructed to form a silicate that can be completely dissolved by acid: Na 1.8 (Mg 0.9 Si 1.1 O 4 ), Na 1.8 (Mg 1.75 Si 1.2 O 4 ), Na 1.8 (Mg 1.5 Si 0.55 O4 ).
[0028] Furthermore, the parameters of the power-on oxidation in S2-3 are: voltage of 300-500 V, power-on time of 5-10 min, current frequency of 600-700 Hz, and duty cycle of 5-6%.
[0029] Description: Micro arc oxidation technology is used to 3 A calcium phosphate oxide coating is deposited on the thin film. The coating has a uniform porous structure. As the voltage increases, a rutile phase is formed in the coating, the micropore size becomes larger, and the pore density decreases, which is similar to CaTiO 3 The interface is well integrated.
[0030] Further, the etching process in S2-4 is as follows:
[0031] First, the porous network CaTiO 3 Porous CaTiO 3 Completely immersed in a NaOH solution with a concentration of 1-3 mol / L, the etching temperature is 50-55°C, and the etching time is 24 hours; then heated to 500-550°C at a heating rate of 10°C / min, and kept warm for 1-1.5 hours.
[0032] Description: Alkaline etching dissolves the surface of the calcium-phosphorus oxide coating, and the TiO 2 With OH - The ions react to form HTiO 3 - Ions, HTiO 3 - The ions further react with the Na + The ion reaction forms a porous network-like sodium titanate hydrate; the subsequent heat treatment changes the surface morphology of the coating, causing the sodium titanate hydrate to dehydrate and crystallize to form Na 2 Ti 9 O 19 Meanwhile, HTiO 3 - The ions further attract dissolved Ca in the alkaline solution. 2+ ions, forming a porous honeycomb-like calcium titanate hydrate on the surface of the coating, thereby greatly enhancing the bonding strength with the polyethylene diaphragm.
[0033] Further, the binder in S2-5 is a mixture of polyvinylidene fluoride and 1-methyl-2-pyrrolidone;
[0034] Let n be the multiplication coefficient and n∈R + , then CaTiO in S2-5 3The amount of the composite material added was 5 n g, the amount of polyvinylidene fluoride added was n [1, 1.5] g, and the amount of 1-methyl-2-pyrrolidone added was n [10, 15] mL;
[0035] The drying parameters in S2-5 are: drying temperature is 60-70°C, and drying time is 12h.
[0036] As another aspect of the present invention, there is also provided a method based on the above-mentioned CaTiO 3 Method for preparing lithium battery using composite diaphragm:
[0037] S3-1, use the punching machine to convert the CaTiO in S2 3 The composite diaphragm was cut into discs with a diameter of 16 mm to obtain CaTiO 3 Composite diaphragm;
[0038] S3-2, LiNi as electrode active material 0.5 Mn 1.5 O 4 , acetylene black as a conductive agent and polyvinylidene fluoride as a binder are placed in 1-methyl-2-pyrrolidone and mixed evenly to prepare a slurry;
[0039] Let n be the multiplication coefficient and n∈R + , then LiNi in S3-3 0.5 Mn 1.5 O 4 The amount of acetylene black added was 8 n g, the amount of polyvinylidene fluoride added was n [1, 1.5] g, and the amount of 1-methyl-2-pyrrolidone added was n [10, 15] mL;
[0040] S3-3, coating the slurry on aluminum foil by a doctor blade method, drying at 80° C. for 6 to 8 hours, and finally cutting into discs with a diameter of 10 mm by a punching machine to obtain electrode sheets;
[0041] S3-4. Prepare an argon atmosphere glove box with a water and oxygen content of less than 0.1 ppm. Assemble the lithium battery components in the glove box in the following order: negative electrode shell, electrode sheet, CaTiO 3 Composite diaphragm sheet, 85μL electrolyte, 10mm lithium sheet, gasket, shrapnel, positive electrode shell; finally, use a sealing machine to seal the lithium battery and store it for later use.
[0042] The beneficial effects of the present invention are:
[0043] The present invention proposes a method for separating CaTiO from blast furnace titanium slag. 3The method for preparing a high-stability solid electrolyte interface layer for lithium batteries has promoted the high-value utilization of blast furnace titanium slag and provided new ideas and methods for the preparation of solid electrolyte interface layers for lithium batteries. The cheap characteristics of blast furnace titanium slag can significantly reduce the cost of CaTiO 3 The price of the product makes it more competitive in the market, and also 3 The microstructure of the film is modified to enhance its bonding strength with the polyethylene separator and improve the thermal stability of the solid electrolyte interface layer of the lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 is a SEM image of the sample prepared in Example 1;
[0045] Figure 2 is a cross-sectional SEM image of the sample prepared in Example 1;
[0046] Figure 3 This is the effect of voltage on the amount of Mn infiltration in the diaphragm interface in the experimental example;
[0047] Figure 4 The PE separator and CaTiO 3 Overpotential diagram of composite separator assembled battery;
[0048] Figure 5 The PE separator and CaTiO 3 Capacity change diagram of composite diaphragm assembled battery during cyclic discharge DETAILED DESCRIPTION
[0049] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0050] Example 1: This example describes a method for separating perovskite from blast furnace titanium slag and preparing battery materials.
[0051] S1, titanium slag impurity removal;
[0052] S1-1, after ball milling, the initial blast furnace titanium slag is ultrasonically cleaned with anhydrous ethanol and deionized water in sequence, and then completely dried and ground into powder for later use, to obtain cleaned titanium slag;
[0053] The parameters of ultrasonic cleaning were as follows: ultrasonic frequency was 40 kHz, cleaning temperature was 45 °C, and cleaning time was 20 min;
[0054] S1-2, the cleaned titanium slag and MnO are placed in a reactor at a molar ratio of Mn:Ti=3:8, and the mixture is evenly mixed by ball milling. After the mixture is evenly mixed, the mixture is placed in a reactor, and then the temperature is increased from room temperature to 1500°C at a heating rate of 3°C / min and kept at this temperature for 1h, and then the temperature is decreased at a cooling rate of 1°C / min until the temperature is decreased to 1250°C, and then the temperature is quenched in a quenching agent to obtain quenched slag after the precipitation of perovskite;
[0055] The parameters of ball milling were as follows: ball mill speed was 200 r / min, ball milling time was 1 h;
[0056] The quenching agent is 20% by mass NaNO 3 and 25% by mass of Na 2 CO 3 Mixed in a volume ratio of 2:1;
[0057] S1-3, the quenched slag is washed with anhydrous ethanol, ball-milled, dried once, acid-leached, filtered, washed with deionized water, and dried twice to obtain CaTiO 3 material;
[0058] The parameters of acid leaching are as follows: leaching temperature is 25°C, leaching liquid is 10% hydrochloric acid by mass, solid-liquid ratio is 1:15, leaching time is 1h, and stirring speed during acid leaching is 400r / min;
[0059] The parameters of ball milling in S1-3 are: ball mill speed is 200r / min, ball milling time is 1h;
[0060] The parameters of primary drying and secondary drying are: drying temperature is 100°C, drying time is 30min;
[0061] S2. Preparation of CaTiO 3 Composite diaphragm;
[0062] S2-1, CaTiO 3 The material was isostatically pressed at 6 MPa into a 0.7 mm thick sheet to obtain CaTiO 3 Thin slices;
[0063] S2-2, calcium glycerophosphate, Ca(CH 3 COO 2 , EDTA-2Na and NaOH are mixed evenly in deionized water to obtain a mixed solution;
[0064] The amount of calcium glycerophosphate added is 10g, Ca(CH 3 COO 2 The amount of added is 11.5g, the amount of added EDTA-2Na is 14.3g, the amount of added NaOH is 9g, and the amount of added deionized water is 1L;
[0065] S2-3, the mixed solution in S2-2 is placed in an arc oxidation device (the device is a product of the prior art) as an electrolyte, a stainless steel tank is used as a working cathode, and the CaTiO 3 The thin sheet is used as the working anode, and finally oxidized by electricity to obtain a porous network of CaTiO 3 ;
[0066] The parameters of the energized oxidation are: voltage 300V, energized time 5min, current frequency 600Hz, duty cycle 5%
[0067] S2-4, the porous network CaTiO 3 Porous CaTiO 3 The samples were completely immersed in a 1 mol / L NaOH solution, the etching temperature was 50 °C, and the etching time was 24 h. Then, the samples were heated to 500 °C at a heating rate of 10 °C / min and kept warm for 1 h. Finally, the CaTiO 3 Composite materials;
[0068] S2-5, CaTiO 3 The composite material and the adhesive were stirred and mixed uniformly, and then sprayed evenly on both sides of the PE (KK1640) diaphragm, and then dried to obtain CaTiO 3 Composite diaphragm;
[0069] The binder is a mixture of polyvinylidene fluoride and 1-methyl-2-pyrrolidone;
[0070] CaTiO 3 The amount of the composite material added was 5 g, the amount of polyvinylidene fluoride added was 1 g, and the amount of 1-methyl-2-pyrrolidone added was 10 mL;
[0071] The drying parameters are: drying temperature is 60°C and drying time is 12h.
[0072] Example 2: This example describes a method for separating perovskite from blast furnace titanium slag and preparing battery materials.
[0073] S1, titanium slag impurity removal;
[0074] S1-1, after ball milling, the initial blast furnace titanium slag is ultrasonically cleaned with anhydrous ethanol and deionized water in sequence, and then completely dried and ground into powder for later use, to obtain cleaned titanium slag;
[0075] The parameters of ultrasonic cleaning were as follows: ultrasonic frequency of 50 kHz, cleaning temperature of 55 °C, and cleaning time of 30 min;
[0076] S1-2, the cleaned titanium slag and MnO are placed in a reactor at a molar ratio of Mn:Ti=4:8, and the mixture is evenly mixed by ball milling. After the mixture is evenly mixed, the mixture is placed in a reactor, and then the temperature is increased from room temperature to 1500°C at a heating rate of 3°C / min and kept at this temperature for 1.5 hours, and then the temperature is decreased at a cooling rate of 2°C / min until the temperature is decreased to 1250°C, and then the mixture is quenched in a quenching agent to obtain quenched slag after the precipitation of perovskite;
[0077] The parameters of ball milling were as follows: ball mill speed was 250 r / min, ball milling time was 1.5 h;
[0078] The quenching agent is 20% by mass NaNO 3 and 25% by mass of Na 2 CO 3 Mixed in a volume ratio of 4:1;
[0079] S1-3, the quenched slag is washed with anhydrous ethanol, ball-milled, dried once, acid-leached, filtered, washed with deionized water, and dried twice to obtain CaTiO 3 material;
[0080] The parameters of acid leaching are as follows: leaching temperature is 25°C, leaching liquid is 10% hydrochloric acid by mass, solid-liquid ratio is 1:20, leaching time is 1h, and stirring speed during acid leaching is 450r / min;
[0081] The parameters of ball milling in S1-3 are: ball mill speed is 250r / min, ball milling time is 1.5h;
[0082] The parameters of primary drying and secondary drying are: drying temperature is 100°C, drying time is 40min;
[0083] S2. Preparation of CaTiO 3 Composite diaphragm;
[0084] S2-1, CaTiO 3 The material was isostatically pressed at 6 MPa into a 1 mm thick sheet to obtain CaTiO 3 Thin slices;
[0085] S2-2, calcium glycerophosphate, Ca(CH 3 COO 2 , EDTA-2Na and NaOH are mixed evenly in deionized water to obtain a mixed solution;
[0086] The amount of calcium glycerophosphate added is 10g, Ca(CH 3 COO 2 The amount of added is 12.8g, the amount of added EDTA-2Na is 15.5g, the amount of added NaOH is 10g, and the amount of added deionized water is 1.2L;
[0087] S2-3, the mixed solution in S2-2 is placed in an arc oxidation device (the device is a product of the prior art) as an electrolyte, a stainless steel tank is used as a working cathode, and the CaTiO 3 The thin sheet is used as the working anode, and finally oxidized by electricity to obtain a porous network of CaTiO 3 ;
[0088] The parameters of the energized oxidation are: voltage 500V, energization time 10min, current frequency 700Hz, duty cycle 6%
[0089] S2-4, the porous network CaTiO 3 Porous CaTiO 3 The samples were completely immersed in a 3 mol / L NaOH solution, the etching temperature was 55°C, and the etching time was 24 h. Then, the samples were heated to 550°C at a heating rate of 10°C / min and kept at this temperature for 1.5 h. Finally, the CaTiO 3 Composite materials;
[0090] S2-5, CaTiO 3 The composite material and the adhesive were stirred and mixed uniformly, and then sprayed evenly on both sides of the PE (KK1640) diaphragm, and then dried to obtain CaTiO 3 Composite diaphragm;
[0091] The binder is a mixture of polyvinylidene fluoride and 1-methyl-2-pyrrolidone;
[0092] CaTiO 3 The amount of the composite material added was 5 ng, the amount of polyvinylidene fluoride added was 1.5 g, and the amount of 1-methyl-2-pyrrolidone added was 15 mL;
[0093] The drying parameters are: drying temperature is 70°C and drying time is 12h.
[0094] Experimental Example: The description of this experimental example is based on the scheme described in Example 1, and is intended to illustrate the relationship between the process parameters of the present invention and the performance of the finished product.
[0095] 1. Test of Mn penetration in arc oxidation interface
[0096] The doping of Mn element can significantly induce the 3 The ferroelectricity of the coating is improved, and its electrochemical ability is enhanced. Therefore, the content of Mn in the interface can show the electrochemical performance of the coating interface, and the amount of Mn doping is related to the voltage during arc oxidation. Figure 1 The relationship shown.
[0097] pass Figure 3It can be seen from the data that as the voltage rises to above 250V, the Mn content increases, and there is a slowing trend when it reaches 330V, and it reaches a low point at 350V, at which the Mn / Ca ratio is the lowest; and as the voltage increases to 450V, the Mn content increases again, and the Mn / Ca ratio increases again, indicating that the Mn / Ca content ratio in the coating interface can be controlled by adjusting the voltage during arc oxidation.
[0098] 2. Thermal stability test of solid electrolyte interface layer of lithium battery
[0099] In order to verify the CaTiO prepared by the present invention 3 Dendrite inhibition effect of composite membrane, using lithium as negative electrode, PE separator and CaTiO 3 Composite membrane assembled battery, at 0.2 mA cm -2 The current density was 0.5, 1, 1.5, 2.0, 2.5, and 3.0 mAh cm-2 on copper foil. -2 The overpotential diagram of lithium is shown in Figure 4 .
[0100] Li-Cu half-cells were assembled to test the nucleation overpotential. The cells were charged at 0.2 mA cm -2 The current density is used for constant current discharge, and the CaTiO 3 The nucleation overpotential of the battery prepared by the composite separator is 65.4mV, which is significantly lower than that of the battery using ordinary PE separator (125.8mV). A smaller nucleation overpotential means a lower nucleation barrier, which is conducive to uniform nucleation during the deposition process, thereby avoiding the formation of dendrites and improving the electrochemical performance of the battery.
[0101] 3. Cycle performance test
[0102] To further explore the CaTiO 3 The dendrite inhibition effect of the composite separator was tested by assembling a 5V full battery with lithium as the reference electrode and counter electrode and LNMO as the positive electrode. 3 The composite diaphragm is coated on one side and the coating surface faces the lithium sheet. The microscopic morphology is shown in Figure 1 , Figure 2 .
[0103] Figure 5 For the use of CaTiO 3 The long cycle performance of the full battery with composite diaphragm and PE diaphragm at 2℃ current density shows that the battery with PE diaphragm shows voltage decay after 320 cycles, and the capacity has decayed to 20.2mAh / g after 500 cycles. 3 The capacity of the full battery with the composite separator is still 80.3 mAh / g after 800 cycles.
[0104] Therefore, it can be seen that CaTiO 3 Composite separators can significantly increase battery capacity and improve battery cycle performance.
[0105] 4. AC impedance test
[0106] In the AC impedance test, the current frequency range is 0.01Hz~1MHz. The impedance test of the battery prepared with the above two separators was carried out at 20 and 50 cycles. The results showed that after 20 cycles, the interface impedance of the battery prepared with ordinary PE membrane was 130.9Ω, while that of the battery prepared with CaTiO 3 The interfacial impedance of the battery prepared with the composite diaphragm was only 49.8Ω; after 50 cycles, the interfacial impedance of the battery prepared with the ordinary PE film increased rapidly to 430.5Ω, while that with the CaTiO 3 The resistance of the battery prepared with the composite separator is only 202.6Ω, indicating that it has good interface stability.
Claims
1. A method for separating perovskite from blast furnace titanium slag and preparing battery materials, characterized in that: Includes steps: S1, titanium slag impurity removal; S1-1, after ball milling, the initial blast furnace titanium slag is ultrasonically cleaned with anhydrous ethanol and deionized water in sequence, and then completely dried and ground into powder for later use, to obtain cleaned titanium slag; S1-2, placing the cleaned titanium slag and MnO in a molar ratio of Mn:Ti=3-4:8 in a reactor and mixing them evenly by ball milling, placing them in a reactor after mixing evenly, and then heating them from room temperature to 1500°C at a heating rate of 3°C / min and keeping the temperature for 1-1.5h, then cooling them at a cooling rate of 1-2°C / min until the temperature drops to 1250°C, and then quenching them in a quenching agent to obtain quenched slag after perovskite precipitation; S1-3, washing the quenched slag with anhydrous ethanol, ball milling, primary drying, acid leaching, filtering, washing with deionized water and secondary drying in sequence to obtain CaTiO3 material; S2, preparing CaTiO3 composite diaphragm; S2-1, isostatically pressing the CaTiO3 material at 6 MPa into a thin sheet with a thickness of 0.7 to 1 mm to obtain a CaTiO3 thin sheet; S2-2, mixing calcium glycerophosphate, Ca(CH3COO)2, EDTA-2Na and NaOH in deionized water to obtain a mixed solution; Let n be the multiplication coefficient and n∈R + , then the amount of calcium glycerophosphate added to the mixed solution is 10 ng, the amount of Ca(CH3COO)2 added is n[11.5,12.8]g, the amount of EDTA-2Na added is n[14.3,.15.5]g, the amount of NaOH added is n[9,10]g, and the amount of deionized water added is n[1,1.2]L; S2-3, placing the mixed solution in S2-2 into an arc oxidation device as an electrolyte, using a stainless steel tank as a working cathode, using the CaTiO3 sheet in S2-1 as a working anode, and finally applying electricity to oxidize to obtain a porous mesh CaTiO3; S2-4, completely immersing the porous mesh CaTiO3 in a NaOH solution for etching, and then crushing to obtain a CaTiO3 composite material; S2-5. After the CaTiO3 composite material and the adhesive are stirred and mixed evenly, the mixture is sprayed evenly on both sides of the PE diaphragm, and then dried to obtain a CaTiO3 composite diaphragm.
2. A method for separating perovskite and preparing battery materials based on blast furnace titanium slag according to claim 1, characterized in that: The parameters of the ultrasonic cleaning described in S1-1 are: ultrasonic frequency of 40 to 50 kHz, cleaning temperature of 45 to 55° C., and cleaning time of 20 to 30 min.
3. A method for separating perovskite and preparing battery materials based on blast furnace titanium slag as claimed in claim 1, characterized in that: The parameters of the ball milling in S1-2 are: the ball mill speed is 200-250 r / min, and the ball milling time is 1-1.5 h; The quenching agent described in S1-2 is a mixture of 20% by mass NaNO3 and 25% by mass Na2CO3 in a volume ratio of 2 to 4:
1.
4. A method for separating perovskite and preparing battery materials based on blast furnace titanium slag according to claim 1, characterized in that: The parameters of the acid leaching in S1-3 are: the leaching temperature is 25° C., the leaching liquid is 10% hydrochloric acid by mass, the solid-liquid ratio is 1:15-20, the leaching time is 1 h, and the stirring rate during the acid leaching is 400-450 r / min; The parameters of the ball milling in S1-3 are: the ball mill speed is 200-250 r / min, and the ball milling time is 1-1.5 h; The parameters of the primary drying and secondary drying in S1-3 are: the drying temperature is 100° C., and the drying time is 30 to 40 minutes.
5. A method for separating perovskite and preparing battery materials based on blast furnace titanium slag as claimed in claim 1, characterized in that: The parameters of the power-on oxidation in S2-3 are: voltage of 300-500V, power-on time of 5-10min, current frequency of 600-700Hz, and duty cycle of 5-6%.
6. A method for separating perovskite and preparing battery materials based on blast furnace titanium slag according to claim 1, characterized in that: The steps of etching process described in S2-4 are: First, the porous mesh CaTiO3 is completely immersed in a NaOH solution with a concentration of 1 to 3 mol / L, the etching temperature is 50 to 55°C, and the etching time is 24 hours; then, it is heated to 500 to 550°C at a heating rate of 10°C / min and kept warm for 1 to 1.5 hours.
7. A method for separating perovskite and preparing battery materials based on blast furnace titanium slag according to claim 1, characterized in that: The binder in S2-5 is a mixture of polyvinylidene fluoride and 1-methyl-2-pyrrolidone; Let n be the multiplication coefficient and n∈R + , then the amount of CaTiO3 composite material added in S2-5 is 5n g, the amount of polyvinylidene fluoride added is n[1,1.5]g, and the amount of 1-methyl-2-pyrrolidone added is n[10,13]mL; The drying parameters described in S2-5 are: drying temperature is 60-70°C, and drying time is 12h.
Citation Information
Patent Citations
Composite diaphragm, preparation method and application
CN112952286A
Lithium metal negative electrode structure, electrochemical device including the same, and method for manufacturing the lithium metal negative electrode structure
JP2022552549A
Preparation method of porous composite separator
US20160064711A1
Lithium Metal Battery
US20200127324A1